Open source software and the New Zealand education system: A response to Roy - Richard Wyles (Flexible Learning Association of New Zealand, 2012)
Software is ubiquitous in twenty-first-century developed societies. Software now permeates all aspects of our lives, from farm production and the telephones we use to the education we receive or deliver. Equitable access to educational technology is a key issue and open source technology is part of the answer.